The Relationship Between Urban Design and Urban Quality of Life: “A Case Study of Kastamonu City- Turkey” - Öztürk, Sevgi; Genç, Zeynep Pınar (Artvin Coruh Universitesi Orman Fakultesi Dergisi, 2015)
The physical, social, and economic components of urban areas determine the characteristics and eligibility of urban life. Urban areas are negatively affected by rapid population growth, unplanned city development, insufficient physical environments, and social, economic and cultural problems. Nowadays, urban planning and design studies are being implemented to find solutions for the cities that lost their identities, became similar to each other, and externalized. These studies organize the physical components of the urban areas and aim to create livable and functional cities. In this study, the relationship between urban design and urban quality of life objectives is investigated in the city of Kastamonu. In this context, a poll was conducted among Kastamonu University students. As a result, it was found that there is a positively high degree (R: 0,776) linear correlation between urban design and quality of life. Moreover, it was observed that different age and gender groups have a different view of the city according to their spatial experiences.
Keywords: Kentsel tasarım; yaşam kalitesi; Kastamonu; Urban design; urban quality; Kastamonu.; 4. Education; 11. Sustainability